Early sexual debut and risky sex in young adults: the role of low self-control - B. M. Magnusson; A. Crandall; K. Evans (BMC, 2019)
Abstract Background The purpose of this study was to examine the role of low self-control as a mediator or moderator between early age at sexual debut and risky sexual behavior in young adulthood. Methods Data on 5734 male and female Add Health participants were used. Self-control (waves 1 & 3), age at sexual debut (wave 3) and risky sexual behavior (wave 4) were used in a structural equation modeling framework to assess the relationships of interest. Results Approximately 17% of respondents were < 15 years at first sexual intercourse. Among females only, both early age at first intercourse (Parent-report: z = 5.08, p < .001; Self-report: z = 2.05, p < .05) and low self-control at wave 3 (Parent-report: z = 2.30, p < .05; Self-report: z = 2.31, p < .05) mediated the relationship between low self-control at wave 1 and risky sexual behaviors in young adulthood. Similarly in the male-only model, both early age at first intercourse (Parent-report: z = 2.92, p < .01; Self-report: z = 3.04, p < .01) and low self-control at wave 3 (Parent-report: z = 1.99, p < .05; Self-report: z = 3.15, p < .01) mediated the relationship between low self-control and risky sexual behaviors in young adulthood. There was evidence of moderation in the male-only model (− 0.26, p < .01), such that lower impulsivity strengthened the relationship between early sex and risky sex. Conclusions This study confirms the role of executive functions in sexual behaviors and suggests that interventions aimed at improving self-control may be beneficial in reducing risky sexual behavior.